Electrical engineering principles : for electrical, telecommunications, and installation technicians - Stott, G. S.; Birchall, G.; Ward, M. R. (London ; New York : McGraw-Hill, 1969)
This book is intended primarily for first and second year electrical technician and telecommunication technician students, and will also be of assistance to students on the first and second years of most mechanical-electrical courses. It covers the revised syllabus for engineering principles of the electrical, radio, and installation technicians' courses and the engineering science and principles 'A' syllabus on the telecommunication technicians' course.
Includes index.
ne 27/04/2018
Loans
Keywords: Electrical Engineering; Telecommunication; Mechanics